2014
DOI: 10.3835/plantgenome2013.10.0030
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association Mapping of Sclerotinia sclerotiorum Resistance in Soybean with a Genotyping‐by‐Sequencing Approach

Abstract: Sclerotinia stem rot (SSR) is one of the most important pests in cool soybean growing regions of the Northeastern United States and Canada. However, the intensity of infestations varies considerably from year to year according to weather conditions, thus making it difficult for breeders to select under uniform disease pressure. Selection for resistance to SSR would be greatly facilitated by the use of molecular markers. In this work, a collection of 130 lines was inoculated using the cotton pad method and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 108 publications
(113 reference statements)
7
158
0
4
Order By: Relevance
“…The minimum number of markers that are required to conduct a successful association analysis depends on the extent of LD over physical distance in a given population. Many factors affect LD such as recombination and mutation rate, relatedness (kinship), gene conversion, selection (natural, artificial, and balancing), mating systems (self or cross pollination), genetic diversity, and population structure [29, 45]. In this study, the average LD decay was approximately 520 and 480 Kb in A t and D t sub-genome, respectively, and genome wide ~500 Kb (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The minimum number of markers that are required to conduct a successful association analysis depends on the extent of LD over physical distance in a given population. Many factors affect LD such as recombination and mutation rate, relatedness (kinship), gene conversion, selection (natural, artificial, and balancing), mating systems (self or cross pollination), genetic diversity, and population structure [29, 45]. In this study, the average LD decay was approximately 520 and 480 Kb in A t and D t sub-genome, respectively, and genome wide ~500 Kb (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Although scientists have successfully identified marker-trait associations using GBS-based SNPs in many plant species [14, 21, 28, 29], so far no GWAS study has been reported in Upland cotton using SNPs. There are a few GWAS studies that were reported using SSR markers in Upland cotton [2, 4, 23, 24, 26, 30] as mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…DArTseq combines genome complexity reduction methods and next-generation sequencing platforms (Courtois et al, 2013;Cruz et al, 2013;Raman et al, 2014;Kilian et al, 2016). Therefore, DArTseq represents a new implementation of sequencing of complexity-reduced representations (Huang et al, 2014) and more recent applications of this concept on the nextgeneration sequencing platforms (Sonah et al, 2013;Bastien et al, 2014).…”
Section: Snp Discovery By Dartseqmentioning
confidence: 99%
“…However, due to the limited coverage of resistance sources, inadequate statistical procedures, and small mapping populations, many QTLs underlying SCN resistance, therefore, have remained un-detected. With the availability of a soybean reference genome sequence and the development of high-throughput single nucleotide polymorphism (SNP) assay platforms, association mapping (AM) has been demonstrated to be a powerful approach to dissect various traits, such as disease resistance, yield, and quality-related traits in soybean (Wen et al 2014(Wen et al , 2015Hao et al 2012a, b;Bastien et al 2014;Hwang et al 2014). Recent genomewide association study (GWAS) on 282 accessions of soybean breeding lines have detected significant signals at two loci corresponding to rhg1 and FGAM1, plus a third locus located at the end (55.9 Mb) of Chr.…”
Section: Introductionmentioning
confidence: 99%